The Correlation of Students’ Vocabulary Mastery, Sentence Structure and The Ability of Composing Descriptions for Middle School Students - Indah Wulan Dari; Surastina Surastina; Tri Riya Anggraini; Galuh Dwi Ajeng (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
The problem raised in this study is the correlation between vocabulary and sentence mastery and the ability to compose descriptions. This research was conducted because of the reality in the field that the ability to compose descriptions and mastery of vocabulary, as well as sentences that need to be developed. This study aims to describe the correlation between vocabulary mastery and sentence structure with the ability to compose descriptions of eighth grade students of SMPN 02 Waway Karya, East Lampung. To achieve the research objectives mentioned above, the authors use the correlational method, meaning that data is collected after all the events in question have taken place. The techniques used in collecting the data are questionnaires, tests, and observations. The data analysis techniques include requirements analysis test, statistical analysis, and research hypothesis testing techniques. Based on the results of the study, it can be concluded that, (1) there is a positive and significant correlation between sentence structure and the ability to compose descriptions, indicated by a correlation coefficient of 0.766 and a coefficient of determination (R2) of 0.587 or 58.7%, (2) there are a positive and significant correlation between vocabulary mastery and the ability to compose a description shown by a correlation coefficient of 0.662 and a coefficient of determination (R2) of 0.438 or 43.8%, (3) there is a positive and significant correlation between vocabulary mastery and sentence structure with the ability to compose a description shown by the correlation coefficient of 0.804 and the coefficient of determination (R 2 ) of 0.646 or 64.6%.